Tobacco Health Literacy and Smoking Behaviors among High School Students, Pathum Thani Province - จันนันทะ สิริญ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This cross-sectional survey research aims 1. To assess health literacy regarding cigarette smoking among high school students in Pathum Thani Province. To investigate smoking behaviors among high school students in Pathum Thani Province. 3. To compare health literacy scores regarding cigarette smoking between smoking and non-smoking high school students in Pathum Thani Province. The study was conducted during the first semester of the 2025 academic year with 582 high school students. Data were collected via an online questionnaire and analyzed using descriptive statistics and independent samples t-test, with a statistical significance level set at less than .05. The findings revealed that: 1) 18.6% of the students (n = 108) had smoking experience, with electronic cigarettes and conventional cigarettes being the two most common types used; 2) the majority of students (81.8%) exhibited a moderate level of tobacco health literacy; and 3) students who had never smoked demonstrated significantly higher tobacco health literacy scores than students who smoked in the domains of self-management, media literacy, and communication (p < .05).